2006
DOI: 10.1007/s11257-006-9012-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of learning styles on student grouping for collaborative learning: a case study

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in: Abstract.Learning style models constitute a valuable tool for improving individual learning by the use of adaptation techniques based on them. In this paper we present how the benefit of considering learning styles with adaptation purposes, as part of the user model, can be extended to the context of collaborative learning as a key feature for group formation. We explore the effects that the combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
0
18

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(137 citation statements)
references
References 52 publications
6
113
0
18
Order By: Relevance
“…Students with a similar proficiency level will have convergent needs of teaching content and pace. While the findings reported by Alfonseca et al (2006) support mixing students based on their learning styles, we argue that this grouping method is plausible for group tasks involving a very small number of group members. For a large class with about 100 students (which is usually the case in College English classes), it is better to group students homogeneously, while in break-out sessions or group projects, we could mix them to develop their less preferred styles (Felder & Spurlin, 2005).…”
Section: Grouping Students In Efl Classesmentioning
confidence: 56%
See 1 more Smart Citation
“…Students with a similar proficiency level will have convergent needs of teaching content and pace. While the findings reported by Alfonseca et al (2006) support mixing students based on their learning styles, we argue that this grouping method is plausible for group tasks involving a very small number of group members. For a large class with about 100 students (which is usually the case in College English classes), it is better to group students homogeneously, while in break-out sessions or group projects, we could mix them to develop their less preferred styles (Felder & Spurlin, 2005).…”
Section: Grouping Students In Efl Classesmentioning
confidence: 56%
“…Research results show that group heterogeneity by mixing students with different learning styles is conducive to better performance (e.g., Alfonseca et al, 2006). On the other hand, research also attests to the fact that students in a homogeneous group based on the proficiency level significantly outperformed students in a heterogeneous group (Baer, 2003).…”
Section: Grouping Students In Efl Classesmentioning
confidence: 83%
“…In our work, we build the user model based on the user knowledge as well as their actions in MOT 2.0. Furthermore, the work in (Alfonseca et al 2006) suggested the possibility of improving collaborative learning, by grouping students in specific ways, based on information stored in their user models. In MOT 2.0, the grouping mechanism is slightly different, as it is based on the given course.…”
Section: Related Researchmentioning
confidence: 99%
“…Uno de los modelos de estilos de aprendizaje más utilizados es el propuesto por Felder-Silverman [Felder and Silverman 1988]. Por ejemplo, este modelo es aplicado en [Alfonseca et al 2006, Martin and Paredes 2004, Monteserin et al 2010. El primer trabajo explora los efectos que puede producir el hecho de combinar estudiantes con diferentes estilos de aprendizaje sobre los resultados del trabajo en grupo.…”
Section: Trabajos Relacionadosunclassified